Astrocytes engage unique molecular programs to engulf pruned neuronal debris from distinct subsets of neurons. - Tasdemir-Yilmaz, O.E.; Freeman, M.R. (Genes & Development, 2014)
Precise neural circuit assembly is achieved by initial overproduction of neurons and synapses, followed by refinement through elimination of exuberant neurons and synapses. Glial cells are the primary cells responsible for clearing neuronal debris, but the cellular and molecular basis of glial pruning is poorly defined. Here we show that Drosophila larval astrocytes transform into phagocytes through activation of a cell-autonomous, steroid-dependent program at the initiation of metamorphosis and are the primary phagocytic cell type in the pupal neuropil. We examined the developmental elimination of two neuron populations-mushroom body (MB) ? neurons and vCrz? neurons (expressing Corazonin [Crz] neuropeptide in the ventral nerve cord [VNC])-where only neurites are pruned or entire cells are eliminated, respectively. We found that MB ? axons are engulfed by astrocytes using the Draper and Crk/Mbc/dCed-12 signaling pathways in a partially redundant manner. In contrast, while elimination of vCrz? cell bodies requires Draper, elimination of vCrz? neurites is mediated by Crk/Mbc/dCed-12 but not Draper. Intriguingly, we also found that elimination of Draper delayed vCrz? neurite degeneration, suggesting that glia promote neurite destruction through engulfment signaling. This study identifies a novel role for astrocytes in the clearance of synaptic and neuronal debris and for Crk/Mbc/dCed-12 as a new glial pathway mediating pruning and reveals, unexpectedly, that the engulfment signaling pathways engaged by glia depend on whether neuronal debris was generated through cell death or local pruning.